Disulfide Dimerization of Neuronal Calcium Sensor-1: Implications for Zinc and Redox Signaling - Viktoriia E. Baksheeva (MDPI AG, 2021)
Neuronal calcium sensor-1 (NCS-1) is a four-EF-hand ubiquitous signaling protein modulating neuronal function and survival, which participates in neurodegeneration and carcinogenesis. NCS-1 recognizes specific sites on cellular membranes and regulates numerous targets, including G-protein coupled receptors and their kinases (GRKs). Here, with the use of cellular models and various biophysical and computational techniques, we demonstrate that NCS-1 is a redox-sensitive protein, which responds to oxidizing conditions by the formation of disulfide dimer (dNCS-1), involving its single, highly conservative cysteine C38. The dimer content is unaffected by the elevation of intracellular calcium levels but increases to 10–30% at high free zinc concentrations (characteristic of oxidative stress), which is accompanied by accumulation of the protein in punctual clusters in the perinuclear area. The formation of dNCS-1 represents a specific Zn2+-promoted process, requiring proper folding of the protein and occurring at redox potential values approaching apoptotic levels. The dimer binds Ca2+ only in one EF-hand per monomer, thereby representing a unique state, with decreased α-helicity and thermal stability, increased surface hydrophobicity, and markedly improved inhibitory activity against GRK1 due to 20-fold higher affinity towards the enzyme. Furthermore, dNCS-1 can coordinate zinc and, according to molecular modeling, has an asymmetrical structure and increased conformational flexibility of the subunits, which may underlie their enhanced target-binding properties. In HEK293 cells, dNCS-1 can be reduced by the thioredoxin system, otherwise accumulating as protein aggregates, which are degraded by the proteasome. Interestingly, NCS-1 silencing diminishes the susceptibility of Y79 cancer cells to oxidative stress-induced apoptosis, suggesting that NCS-1 may mediate redox-regulated pathways governing cell death/survival in response to oxidative conditions.